Analysis of the Level of Participation and Perception of the Perupuk Village Community in Baru Bara Regency Towards the Management of Pantai Sejarah Nature Tourism - Aulia Rahmi; Rahmawaty Rahmawaty; Zulkifli Lubis (TALENTA Publisher, Universitas Sumatera Utara, 2025)
The management of natural tourism has one goal; one of the main objectives of natural tourism management is to increase local community income, which is closely linked to community participation and perception. This research aims to analyze the level of perception and participation of the Perupuk Village community towards the development of natural tourism at the Pantai Sejarah in Perupuk Village, Batu Bara Regency. This study employed a questionnaire-based interview method with 100 respondents for participation levels and 100 respondents for perception levels, including both residents and visiting tourists. The sample size was determined using Slovin's formula. In addition, direct observations were conducted to study the habits of a group of people in the vicinity of the Pantai Sejarah location, including residents, visiting tourists, traders, and tourism managers. Meanwhile, the relationship between perception, participation, and respondent characteristics was analyzed using Spearman's Rank Correlation Test. The results obtained from this research indicate that the participation level of the Perupuk Village community was high (62.22%), while the perception level was moderate (59.64%). The correlation test results indicate no significant relationship between participation and public perception. These findings suggest that while community participation and perception levels are relatively high, demographic factors such as age, gender, and Education have minimal influence. Further studies should explore strategies to enhance community engagement in tourism development.